2004
DOI: 10.1002/acp.1074
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effectiveness of two suggestibility paradigms in predicting preschoolers' tendency to report a non‐experienced event

Abstract: This study compared the effectiveness of two standardized suggestibility paradigms in predicting preschoolers' tendency to report an independent, non-experienced event. Ninety-three children, aged 47 to 64 months, were given a description of a non-experienced event and were subsequently asked to recall that event in response to cued-recall questions. Four weeks later, half the children were administered the Video Suggestibility Scale for Children (VSSC;Scullin & Ceci, 2001), which consists of yes/no questions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This Wnding was not replicated in children's responses regarding false new details and incorporation of false information about the experienced event. In another study, Miles, Powell, and Stokes (2004) found a similar pattern when the format of the VSSC yield questions included both yes/no and cued recall questions. SpeciWcally, both types of yield questions were equally predictive of false new (i.e., child-generated) details about a nonexperienced event that was suggested by an interviewer Neither version of yield, however, predicted children's repetition of interviewer-supplied details about the nonexperienced event.…”
Section: Yield and Shift Suggestibilitymentioning
confidence: 51%
See 1 more Smart Citation
“…This Wnding was not replicated in children's responses regarding false new details and incorporation of false information about the experienced event. In another study, Miles, Powell, and Stokes (2004) found a similar pattern when the format of the VSSC yield questions included both yes/no and cued recall questions. SpeciWcally, both types of yield questions were equally predictive of false new (i.e., child-generated) details about a nonexperienced event that was suggested by an interviewer Neither version of yield, however, predicted children's repetition of interviewer-supplied details about the nonexperienced event.…”
Section: Yield and Shift Suggestibilitymentioning
confidence: 51%
“…Further research must determine whether the DCCS task should be added to the VSSC protocols, whether there are diagnostically valid cut scores on yield and shift that can identify on an individual level children who may be prone to accepting interviewer suggestions, and whether special precautions for interviewing children above these cut scores can be implemented (e.g., Pipe & Salmon, 2002). These Wndings add to the literature on the predictive validity of the VSSC in preschool children (McFarlane & Powell, 2002;Miles et al, 2004;Scullin et al, 2002) and may help to explain why yield has consistently been found to be a better predictor of suggestibility across situations.…”
Section: Construct Validity Of the Vssc And Children's Inhibitory Conmentioning
confidence: 79%
“…Isolating the best method, and precise value, of mimicking abused children's response styles is obviously important for instructing persons how to play the role of children in simulated interviews, and it is also important for the establishment of a standardized measure of interviewer performance. Currently no such measure exists despite the fact that there are standardized tools for assessing witness performance (Miles, Powell, & Stokes, 2004). Consideration of the value of mock interviews for both educative and assessment purposes is important because the two may not be compatible.…”
Section: Discussionmentioning
confidence: 99%